The personal letter as a source for the history of women in Ireland, 1750 - 1830 - Maxwell, Jane (Trinity College (Dublin, Ireland). Department of History, 2017)
The historiography of women in eighteenth-century Ireland has arrived at a key point. In fewer than fifty years it has come close to centre stage on a strengthening foundation of social history. Biography, with its restricted relevance, and surveys, with their necessary effacement of detail, have now begun to be joined by focussed work on some women in smaller groups, with a tight chronological or geographical setting permitting the gravitational pull of the groups to be assessed. Scholarship in England that revealed nuance and contingency to be the key descriptors of women’s has been echoed in Ireland. The question is, where will the work go from here? Decades ago, early historians of Irish women queried the failure to follow where most of the surviving records led - to the history of the domestic life of wealthy women. Work has begun in this area, and there is more to do, but the record is so fragmentary that there may be a limit to how much more richness remains to be discovered from a surface reading of the documentary evidence. However, if we do not limit ourselves to a study of the surfaces, new vistas open up. If the history of the letter, and of the use of the letter, are studied in their social contexts, with reference to women’s distinctive epistolary practices, further insight will be forthcoming about women’s changing experiences in the period. The eighteenth century is a vital period in Irish women’s history. No less a word than revolution can describe the change that can be observed in their lives. It is a revolution which has not been fully articulated and it is one which may be principally observed in the private domestic setting.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin